THE INFLUENCE OF TAXPAYER AWARENESS AND TAX SANCTIONS ON MOTOR VEHICLE TAXPAYER COMPLIANCE AT UPTD SAMSAT MANDAU DURI BENGKALIS RIAU - Gembira Marbun; Maria Rosani Simbolon (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This study aims to test how much influence taxpayer awareness and tax sanctions have on motor vehicle tax compliance at UPTD. Samsat Mandau Duri. The sampling technique is by incidental sampling according to the predetermined criteria with a sample size of 100 taxpayers who have motorized vehicles and are registered at the Samsat Mandau Duri Office. Data obtained from Samsat Mandau Duri from 2019 to 2022. The analysis technique used in this study is multiple linear regression with a significance level of 5%. Based on the results of the t-test, it shows that Taxpayer Awareness has a positive and significant effect on Motor Vehicle Tax Compliance with a value of ????ℎ????????????????g 2.723 > ???????????????????????? 1.984 and a significance level of 0.008 > 0.05, Tax Sanctions have a positive and significant effect on Motor Vehicle Tax Compliance with a value of ????ℎ????????????????g 6.568 > ???????????????????????? 1.984 and a significance level of 0.000 < 0.05. Based on the results of the F test, it shows that Taxpayer Awareness and Tax Sanctions simultaneously have a significant effect on Motor Vehicle Tax Compliance with a value of ????ℎ????????????????g 30.161 > ???????????????????????? 3.09 and a significance level of 0.000 <0.05.